Pengaruh Metode Round Robin terhadap Hasil Belajar IPS Siswa Kelas VII - Nahdatul Hazmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of Round Robin on student learning outcomes in social studies subject matter VII Class SMP Negeri 2 Situjoah District Limo Nagari. The quantitative method used in this study is an experimental approach, in which the research design is to use a control class as a comparison of the research class. Based on the research results from the analysis it was concluded that the cooperative learning technique of Round Robin d can improve students' social learning outcomes well. Class VII student learning outcomes in SMP N 02 Kec. Situjuah Limo Nagari was divided into two groups: the first was the experimental class where the mean score was 72.9 and the second was the control class where the average value was 60.3. Means the value of the experimental class is higher than the control value because the experimental class uses the Round Robin s method while the control class uses conventional. Conclusions, that by using the Round Robin method in social studies subjects can be said to have a significant effect on learning outcomes. Keywords: Round Robin Method, Learning Outcomes, Social Studies